ABOUT EXPANSION BY EIGEN FUNCTIONS SELF-ADJOINT DIFFERENTIAL OPERATOR'S WITH COEFFICIENTS HAVING PRECISE BEHAVIOUR IN INFINITY - Petrosyan, A. H.; Khachatryan, L. G. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2003)
In $L^2(\mathbb R)$ space an m≥2 order self-adjoint differential operator is observed, the coefficients of which have precise behaviour in infinity. A Fourie expansion formula is derived by means of minimal system of general eigen functions of this operator.
Keywords: self-adjoint differential operator; general eigen functions; Fourie expansion